Back to the Future: Australian Border Policing Under Labor, 2007–2013. (1st April 2014) - ,
Abstract : This article analyses the border policies of australia's federal Labor governments between 2007 and 2013. It argues that the policies of externalization pursued by Labor inevitably led to the restoration of the Pacific Solution introduced by the previous Liberal-National Party Coalition government and reproduced similar forms of state criminality and resistance.